2007
DOI: 10.1074/jbc.m700053200
|View full text |Cite
|
Sign up to set email alerts
|

Bax Inhibitor-1 Regulates Endoplasmic Reticulum Stress-associated Reactive Oxygen Species and Heme Oxygenase-1 Expression

Abstract: The Bax inhibitor-1 (BI-1) is an anti-apoptotic protein that is located in endoplasmic reticulum (ER) membranes and protects cells from ER stress-induced apoptosis. The ER is associated with generation of reactive oxygen species (ROS) through oxidative protein folding. This study examined the role of BI-1 in the regulation of ER stress-induced accumulation of ROS and expression of unfolded protein response-associated proteins. BI-1 reduced the expression levels of glucose response protein 78, C/EBP homologous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
113
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 115 publications
(122 citation statements)
references
References 36 publications
8
113
0
1
Order By: Relevance
“…Inversely, BI-1 knockout cells exhibited hypersensitivity to the same ER stresses, indicating BI-1 aids to inhibit ER stress signalling pathways ( Figure 2b, Table 1) (Chae et al, 2004;Bailly-Maitre et al, 2006). Lee et al (2007) demonstrated that BI-1 can interfere with all three ER signalling pathways ( Figure 2b, Table 1). During ER stress BI-1 overexpression decreased the level of IRE1 expression with downstream repercussions on the activation of XBP-1 and proapoptotic signalling through JNK phosphorylation (Lee et al, 2007).…”
Section: Bi-1 Modulation Of Er Stress-induced Apoptosismentioning
confidence: 91%
See 4 more Smart Citations
“…Inversely, BI-1 knockout cells exhibited hypersensitivity to the same ER stresses, indicating BI-1 aids to inhibit ER stress signalling pathways ( Figure 2b, Table 1) (Chae et al, 2004;Bailly-Maitre et al, 2006). Lee et al (2007) demonstrated that BI-1 can interfere with all three ER signalling pathways ( Figure 2b, Table 1). During ER stress BI-1 overexpression decreased the level of IRE1 expression with downstream repercussions on the activation of XBP-1 and proapoptotic signalling through JNK phosphorylation (Lee et al, 2007).…”
Section: Bi-1 Modulation Of Er Stress-induced Apoptosismentioning
confidence: 91%
“…Lee et al (2007) demonstrated that BI-1 can interfere with all three ER signalling pathways ( Figure 2b, Table 1). During ER stress BI-1 overexpression decreased the level of IRE1 expression with downstream repercussions on the activation of XBP-1 and proapoptotic signalling through JNK phosphorylation (Lee et al, 2007). Moreover BI-1 was shown to bind IRE1 through its C-terminus (Lisbona et al, 2009), which regulates its ability to oligomerize, thereby blocking its RNase activity.…”
Section: Bi-1 Modulation Of Er Stress-induced Apoptosismentioning
confidence: 92%
See 3 more Smart Citations